Analisis Determinan Permintaan Masyarakat Kota Medan Terhadap Jasa Pengiriman Paket Pos Pada PT. Pos Indonesia (Persero) - Kristin Yenita Purba (Jurnal Manajemen Akuntansi (JUMSI), 2023)
PT. Pos Indonesia (Persero) is a state-owned company engaged in delivery services, this company is well known by the wider community as a means of communication and also provides goods delivery services. This study aims to analyze the effect of price, per capita income, population on the demand for postal parcel delivery services at PT. Pos Indonesia (Persero) Medan. The data used in this research is secondary data from 2015 – 2020. The analytical tool used is multiple regression analysis. The software used to carry out the analysis is eviews 9. The results of this study show that the price variable has a negative and significant effect on delivery services. Per capita income variable has a positive and significant effect on delivery services. And the population variable has a negative and insignificant effect on delivery services. As an effort to improve delivery services, business innovation is needed to increase demand for postal parcel delivery services in the face of increasingly fierce competition in the delivery service market. And improve the quality and quality of service as well as affordable prices to meet the demand for delivery services. Satisfaction is very important in increasing the demand for delivery services, therefore it is hoped that the level of service will be further improved.